Autonomie des individus, rapports sociaux de domination et dictatures de masse: les apports d’Alf Lüdtke, historien braconnier - Kott, Sandrine; Fridenson, Patrick (Sociétés politiques comparées. Revue européenne d’analyse des sociétés politiques, 2020)
Alf Lüdtke nous a quittés en janvier 2019. Il est l’un des représentants les plus connus de l’histoire du quotidien en Allemagne (Alltagsgeschichte) et a laissé sa marque dans l’historiographie française et internationale avec la notion d’Eigensinn. Cet article retrace sa trajectoire intellectuelle en mettant en avant son apport dans l’analyse de la domination comme pratique sociale et la manière dont il a pensé l’autonomie des individus dans une perspective d’anthropologie historique. Autonomy of individuals, social relations of domination and mass dictatorships. The contributions of Historian-Poacher Alf Lüdtke Alf Lüdtke died in January 2019. He was one of the most internationally renowned representatives of history of everyday life (Alltagsgeschichte) in Germany and has influenced French and international historiography through the notion of Eigensinn. This article traces his intellectual trajectory by showing Lüdtke’s contributions to the analysis of domination as social practice, and the way he reflected upon the autonomy of individuals in a historical anthropology perspective.